THE AESTHETICS OF PERVERSION: BLACK WOMEN’S QUEST FOR NEW SPACES OF REPRESENTATION - WIRBA IBRAHIM MAINIMO (IJRDO- Journal of Educational Research, 2019)
Up till recently, African literature has preoccupied itself largely with the burning political issues of the day: colonialism, post-colonialism, nationalism and post-independence political gimmickry. Issues related to sexuality have been enshrouded in too many silences. The situation is compounded by the heritage of the oral tradition: the traditional pre-colonial African societies tented to subject issues related to human sexuality to stern taboo laws. However, African women’s literature, due to the radical militancy that presently rages and pervades all its nooks and cranny, has broken the silence by focusing on inversion as a central thematic concern. The theme of sapphism functions within the context of other numerous taboo themes that are found in present-day African women’s literature passim such as pedophilia, child sexual/commercial exploitation, incestuous rape, sexist necrophilia, among many others. This paper seeks to investigate the emergence of the theme of sapphism in Calixthe Beyala’s fiction, the new avenues afforded by it, and how it has pushed the boundaries of African women’s literature. It reveals that the woman’s treatment of this theme marks her conscious attempt to open up new spaces or ways of representation in African literature in a bid to chart the path toward what may be hazarded as a new literary canon.